Pediatric Cardio-Oncology Medicine: A New Approach in Cardiovascular Care - Hugo R. Martinez; Gary S. Beasley; Jason F. Goldberg; Mohammed Absi; Kaitlin A. Ryan; Karine Guerrier; Vijaya M. Joshi; Jason N. Johnson; Cara E. Morin; Caitlin Hurley; Ronald Ray Morrison; Parul Rai; et al. (Children, 2021)
Survival for pediatric patients diagnosed with cancer has improved significantly. This achievement has been made possible due to new treatment modalities and the incorporation of a systematic multidisciplinary approach for supportive care. Understanding the distinctive cardiovascular characteristics of children undergoing cancer therapies has set the underpinnings to provide comprehensive care before, during, and after the management of cancer. Nonetheless, we acknowledge the challenge to understand the rapid expansion of oncology disciplines. The limited guidelines in pediatric cardio-oncology have motivated us to develop risk-stratification systems to institute surveillance and therapeutic support for this patient population. Here, we describe a collaborative approach to provide wide-ranging cardiovascular care to children and young adults with oncology diseases. Promoting collaboration in pediatric cardio-oncology medicine will ultimately provide excellent quality of care for future generations of patients.